Prevalensi Kelainan Refraksi pada Siswa SD Negeri 09 Pagi Tanah Tinggi Jakarta Pusat - Saskia Nassa Mokoginta; Himmi Marsiati; Atiek Indriawati; Tri Panjiasih Susmiarsih (Lembaga Penelitian Universitas YARSI, 2017)
Based on survey results of the Ministry of Health of the Republic of Indonesia reported in 1996 the highest prevalence of eye disease is refractive disorder, which is 24.72%. An estimated 12 million children from 19 million children suffering from blindness have refractive disorders.The purpose of this study is to obtained the prevalence of refractive disorder in children of State Elementary School Tanah tinggi 09 Central Jakarta. Refractive examination was conducted on 103 children at SD Negeri 09 Tanah Tinggi with 7-12 years old using Snellen Chart, LEA Chart, Autorefractors meter and Streak retinoscopy and also given glasses correction with glasses supplied. The prevalence of refractive abnormalities has been obtained from the refractive examination.There were 103 children examined, 53 of them suffering from refractive disorder with 51,46%. From the 53 people, 47 people with 88,68% diagnose with myopia simplex and 6 people with 11,32% was diagnose with Astigmatisme Myopia Compositus. Prevalence of refraction disorder based on Degrees of myopia, we found 46 people with low myopia (less than 3.00 Diopter), moderate (3 - 5 Diopter) and 2 people with high myopia (more than 6 Diopter) Diopters). The prevalence of Refractive Abnormalities in children at SD Negeri 09 Tanah Tinggi is quite high at 51.46%.